Economic and Sociocultural Aspects of Cowrie Currency of the Dagaaba of Northwestern Ghana - Emmanuel Yiridoe (Nordic Journal of African Studies, 1995)
The cowrie currency, the dominant medium of exchange in Ghana before the introduction of the West African Pound and, later, the Cedi, is now merely a vestigial relic in virtually all of modern Ghana except among the Dagaaba. This paper provides an insider's perspective on the economic importance and on the unique role of the cowrie currency among the Dagaaba that explains its perpetual presence. Cultural uses create a derived demand for cowries. Government policies result in debasement of the cedi and, together with monetary characteristics of the cowrie, lead to competition between the cedi and the cowrie.